Neuroleptic syndrome among patients receiving antipsychotic drugs-review - Yuabova, Marina (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2016)
Neuroleptic Malignant Syndrome is occasional but deadly reaction, which results from treatment with antipsychotic medications. Risk aspects include the following: dehydration, agitation, and history of neuroleptic malignant syndrome.  Despite the fact that Neuroleptic Malignant Syndrome has been described as adverse effect from treatment with antipsychotic medications, patients suffering with chemical imbalance of brain or mood disorders, especially when treated with lithium, fall in to higher risk group. Standard criteria for the diagnosis of Neuroleptic Malignant Syndrome highlight the following signs and symptoms: muscle rigidity, hyperthermia, alteration in mental status, and autonomic dysfunction.  Syndrome usually lasts from 7 to 10 days in simple and uncomplicated patients who receiving neuroleptics orally.  Early detection and diagnosis of syndrome are up the most importance, where discontinuance of triggering medication, managing of fluid balance, control of body temperature and close observation for complications takes place.  Use of dopamine agonists should be advised in more complex cases.  Electroconvulsive therapy has also been effective in a few cases.  In this article author reviews the proposed pathology, symptoms, complications, and treatment of Neuroleptic malignant syndrome